LGR6 is a potential diagnostic and prognostic marker for esophageal squamous cell carcinoma. Issue 4 (9th January 2020) - Chai, Tianci; Shen, Zhimin; Zhang, Zhenyang; Chen, Sui; Gao, Lei; Zhang, Peipei; Lin, Wenwei; Kang, Mingqiang; Lin, Jiangbo
Abstract: Background: Leucine‐rich repeat–coupled receptor 6 (LGR6) is a marker of the skin, nails, and other types of adult tissue stem cells and has been widely found to be related to the development and progression of a variety of cancer types. The clinical significance and biological function of LGR6 in esophageal squamous cell carcinoma (ESCC) have not been determined. Methods: The expression of LGR6 at the transcriptional level was analyzed by searching the TCGA and UCSC data sets. Immunohistochemistry, WB, and q‐PCR were used to detect the expression of LGR6 in ESCC and adjacent normal tissues. LGR6 PPI networks and KEGG pathways were used to analyze the potential biological functions of LGR6. Results: The expression of LGR6 in ESCC tissues was significantly higher than that in normal tissues and was negatively correlated with the differentiation degree of ESCC and the prognosis of the patients but not closely correlated with the TNM stage of ESCC. PPI networks showed that LGR6 had a close interaction with RSPO1, RSPO2, RSPO3, and RSPO4. KEGG pathway analysis showed that LGR6 activated the Wnt/β‐catenin signaling pathway by binding with RSPO ligands to promote the progression of ESCC. Conclusion: LGR6 can serve as a potential diagnostic and prognostic marker for ESCC.